2014
DOI: 10.2754/avb201483010009
|View full text |Cite
|
Sign up to set email alerts
|

Testing of inhibition activity of essential oils against Paenibacillus larvae – the causative agent of American foulbrood

Abstract: American foulbrood is a dangerous world-wide spread disease of honey bees caused by the Paenibacillus larvae bacterium. Antibiotic treatments are less effective and leave residues in bee products. It is therefore necessary to find an alternative, especially using natural ingredients such as plant essential oils, probiotics, fatty or organic acids. Two strains of P. larvae were used for this study: CCM 4488, a strain from the Czech collection of micro-organisms and a Slovak field strain which was isolated from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The authors demonstrated in their study that relatively low concentrations of carvacrol-and thymol-based feed additives had a positive effect on the growth performance of trout with apparent effects towards antioxidant defence and innate immunity status. Kuzysinova et al (2014) studied the inhibitory activity of sage (Salvia officinalis), anise (Pimpinella anisum), oregano (Origanum vulgare), caraway (Carum carvi), thyme (Thymus vulgaris), rosemary (Rosmarinum officinalis), clove (Syzygium aromaticum), camomile (Chamomilla recutita), and fennel (Foeniculum vulgare) against Paenibacillus larvae attacking honey bees. They demonstrated in an in vitro study (disc method using 5 a 10 μl essential oil) that certain essential oils (Thymus vulgaris, Origanum vulgare) have inhibitory effects on P. larvae and may be therefore used for the prevention of this disease.…”
Section: Zootechnical Additivesmentioning
confidence: 99%
“…The authors demonstrated in their study that relatively low concentrations of carvacrol-and thymol-based feed additives had a positive effect on the growth performance of trout with apparent effects towards antioxidant defence and innate immunity status. Kuzysinova et al (2014) studied the inhibitory activity of sage (Salvia officinalis), anise (Pimpinella anisum), oregano (Origanum vulgare), caraway (Carum carvi), thyme (Thymus vulgaris), rosemary (Rosmarinum officinalis), clove (Syzygium aromaticum), camomile (Chamomilla recutita), and fennel (Foeniculum vulgare) against Paenibacillus larvae attacking honey bees. They demonstrated in an in vitro study (disc method using 5 a 10 μl essential oil) that certain essential oils (Thymus vulgaris, Origanum vulgare) have inhibitory effects on P. larvae and may be therefore used for the prevention of this disease.…”
Section: Zootechnical Additivesmentioning
confidence: 99%
“…It is therefore necessary to find an alternative, especially using natural ingredients (Kuzyšinová et al 2014). The phenolic compounds of sea buckthorn represent the main group of phytochemicals which exhibit antibacterial and also antiviral effects.…”
Section: Antibacterial and Antiviral Effectsmentioning
confidence: 99%
“…This forces the development of alternative, natural strategies for the prevention and control of AFB. Therefore, studies have been published that suggest application of essential oils (Fuselli et al, 2008;Chirila et al, 2011;Maggi et al, 2011;Gende et al, 2014;Kuzyšinová et al, 2014;Santos et al, 2014;Ansari et al, 2015), plant extracts (González and Marioli, 2010;Damiani et al, 2014;Hernández-López et al, 2014;Anjum et al, 2015;Piana et al, 2015), propolis (Antúnez et al, 2008;Bastos et al, 2008;Mihai et al, 2012;Bíliková et al, 2013;Wilson et al, 2015) or probiotics (Alonso-Salces et al, 2017;Daisley et al, 2020). In addition, in vitro studies showed antimicrobial activity of royal jelly from different geographical origins against P. larvae (Bachanová et al, 2002;Bíliková et al, 2009).…”
Section: Detection and Treatment Of Infected Honey Beesmentioning
confidence: 99%